2020
DOI: 10.1021/acs.analchem.0c03988
|View full text |Cite
|
Sign up to set email alerts
|

Taylor Dispersion Analysis Coupled to Inductively Coupled Plasma-Mass Spectrometry for Ultrasmall Nanoparticle Size Measurement: From Drug Product to Biological Media Studies

Abstract: During last decade, special focus has been laid on ultrasmall nanoparticles for nanomedicine and eventual clinical translation. To achieve such translation, a lot of challenges have to be solved. Among them, size determination is a particularly tricky one. In this aim, we have developed a simple hyphenation between Taylor dispersion analysis and ICP-MS. This method was proven to allow the determination of the hydrodynamic radius of metal-containing nanoparticles, even for sizes under 5 nm, with a relative stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…At tinc=0, the hydrodynamic size of the AGuIX UNSPs is similar in both types of media, illustrating their colloidal stability. Moreover, an absence of interactions with proteins in serum was noticed, as already reported in others papers [27,38,39]. Soon after dilution, a process of biodegradation occurs as asserted by the USNP size decrease.…”
Section: Assessing Different Populations Sizes and Polydispersity Ind...supporting
confidence: 72%
See 3 more Smart Citations
“…At tinc=0, the hydrodynamic size of the AGuIX UNSPs is similar in both types of media, illustrating their colloidal stability. Moreover, an absence of interactions with proteins in serum was noticed, as already reported in others papers [27,38,39]. Soon after dilution, a process of biodegradation occurs as asserted by the USNP size decrease.…”
Section: Assessing Different Populations Sizes and Polydispersity Ind...supporting
confidence: 72%
“…The interface used for TDA consisted in a T-connector where the capillary outlet was inserted through and then connected to the ICP-MS. A sheath liquid (HNO3 1 mM) was added to the junction in order to compensate for the self-aspiration of the nebulizer and to allow quantification without matrix matching as described in [27]. TDA experiments were conducted with an applied mobilization pressure of 50 mbar.…”
Section: Size Measurements By Tda-icp-msmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that Taylor dispersion analysis hyphenation to inductively coupled plasma mass spectrometry (TDA-ICP-MS) is particularly adapted for metal-containing NP size measurements [21,22]. Furthermore, thanks to the selectivity of the technique to metals, TDA-ICP-MS allows size measurements to be performed in complex matrices, rich in proteins, whereas these measurements are often not possible by DLS.…”
Section: Introductionmentioning
confidence: 99%